A Critique of Econometrics. (1st July 2019) - Yu, Bin
Abstract : As a result of the use of mathematical tools, Western econometrics is regarded as a symbol of what is, as well as trends of, real scientific economic research. It has become an excuse and tool for the uncritical maintenance of Western macroeconomics and microeconomics, opposing and marginalizing Marxist political economy. However, mathematics is not derived or used scientifically in econometrics, so the research results are not scientific but ideological. This paper will explore, in addition to the lack of scientific economic foundations, uncritical data use, insufficient philosophical guidance and mathematical foundations, and some other defects that have also existed in econometrics. The application of mathematics in economic research must strictly follow the theory-praxis principles of Marxist political economy, otherwise even minimal deviation may result in wide divergence from aspects of reality analyzed and modeled. Besides, the laws of mathematics must be strictly followed, the limitations of mathematics should be paid attention to, and mathematics should never be applied in ways that hide rather than illuminate reality. Otherwise, nothing will be obtained except chaos, fallacies and ideology-rhetoric.